Analisis Kebutuhan Promosi Kesehatan Deteksi Dini Kanker Serviks dengan Metode Inspeksi Visual Asam Asetat (IVA) - Ira Puspita Artika Sari; Diniati Diniati; Suryani Suryani (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
One way of early detection of cervical cancer is by conducting an IVA test. This research is a qualitative descriptive design that aims to analyze the need for health promotion media for early detection of cervical cancer with the Visual Acetic Acid inspection method that has been carried out in Lidung Village, Sarolangun Regency from January to June 2022. Data collection techniques used in-depth interviews, observation and documentation study. Determination of informants in this study using purposive sampling. Data analysis was carried out by reducing, presenting data and drawing conclusions. Based on in-depth interviews, it can be seen that the awareness of WUS in carrying out the IVA test is still low. One of the factors causing WUS not to carry out the VIA examination is low knowledge. The results of in-depth interviews with several informants revealed that the need for health promotion media regarding early detection of cervical cancer with the visual inspection method acetic acid in Lidung Village is a lecture method. The conclusion of the study is that awareness in the IVA test is low which is caused by low knowledge of the IVA test, the need for health promotion media, namely the lecture method.